Outcomes and reliability of the flow coupler in postoperative monitoring of head and neck free flaps. (8th October 2017) - Fujiwara, Rance J. T.; Dibble, Jacqueline M.; Larson, Scott V.; Pierce, Matthew L.; Mehra, Saral
Abstract : Objectives/Hypothesis: To assess the accuracy and reliability of the flow coupler relative to the implantable arterial Doppler probe in postoperative monitoring of head and neck free flaps. Study Design: Retrospective single‐institution study, April 2015 to March 2017. Methods: Both the venous flow coupler and arterial Doppler were employed in 120 consecutive head and neck free flap cases. When Doppler signal loss occurred, flaps were evaluated by physical exam to determine whether signal loss was a true positive necessitating operating room takeback. Sensitivity, specificity, and false positive rate (FPR) were recorded for each device. Logistic regression was conducted to identify user trends over time. Results: Eleven of 120 patients (9.2%) required takeback, 10 from venous thrombosis and one from arterial thrombosis. Permanent signal loss (PSL) occurred in the flow coupler in all takebacks; PSL occurred in the arterial Doppler only in the case of arterial thrombosis. Salvage rate was 9/11 (81.8%). For the flow coupler, sensitivity was 100%, specificity 86.4%, and FPR 13.6%. For the arterial probe, sensitivity was 9.1%, specificity 97.1%, and FPR 2.9%. A 4.1% decrease in false positives with each additional flow coupler use was observed. Conclusions: Monitoring the vein via flow coupler has high sensitivity in identifying vascular compromise compared to the arterial probe, especially for venous thrombosis. There is moderate FPR; this decreases with increased usage and, when supplemented with physical examination, does not result in unnecessary takebacks. The flow coupler can be a valuable tool in postoperative monitoring of head and neck free flaps. Level of Evidence: 4. Laryngoscope, 128:812–817, 2018